Simultaneously Reducing Cutting Force and Tissue Damage in Needle Insertion With Rotation - Lin, Chi-Lun; Huang, Yu-An (IEEE transactions on biomedical engineering, 2020)
Rotational needle insertion is commonly used in needle biopsy to improve cutting performance. The application of rotational motion for needle insertion has been shown to efficiently reduce the cutting force. However, studies have found that needle rotation can increase tissue damage due to the tissue winding effect. The bidirectional rotation of a needle during insertion can be a solution to avoid tissue winding while maintaining a low cutting force. In this study, needle insertion with bidirectional rotation was investigated by conducting mechanical and optical experiments. First, needle insertion tests were performed on gelatin-based tissue phantom samples to understand the effect of bidirectional needle rotation on the cutting force. Subsequently, the effective strain, which is an indicator of tissue damage, was observed at the cross-sections of samples in the axial and radial directions of the needle by using the digital image correlation (DIC) technology. The primary findings of this study are as follows: (1) higher needle insertion speeds result in higher cutting forces and effective strains that occur at the axial cross-section, (2) increase in the needle rotation reduces the cutting force and effective strain at the axial cross-section but increases the effective strain at the radial cross-section, (3) application of bidirectional rotation decreases the mean effective strain at the radial cross-section by 10%-25% while maintaining a low cutting force. In clinical applications, bidirectional rotation can be a useful strategy to simultaneously reduce the cutting force and tissue damage, which leads to better cutting performance and lower risks of bleeding and hematoma.